Pengaruh Total Quality Management (TQM) terhadap Kinerja Karyawan di BMT Taruna Sejahtera Ungaran, Jawa Tengah - Pratama, Abdul Aziz Nugraha; Maghfiroh, Fira Nur (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
The purpose of this study is to determine the level of TQM and performance in BMT Youth Welfare as well as to determine the effect of TQM on performancein BMT Youth Welfare. Methods of data collection was conducted through a questionnaire distributed to employees of BMT Youth Welfare. Samples is taken as many as 85 respondents by random sampling technique. The data obtained and analyzed using SPSS version 18. This analysis includes test reliability,validity, regression, statistical test through t-test, F-test well as the determinant coefficient (R2) and classical assumptions test. T-test test results showed that the obsession with quality, scientific approach, education and training, freedom of control, involvement and empowerment of employees partially positive and significant influence on employee performance. F-test test showed an obsession with quality, scientific approach, education and training, freedom of control, involvement and empowerment of employees simultaneously significant effect on the performance of employees with effect as of sisianya 89.3% 10.7% influenced by other variables outside the model